A Review of Epidemiological Research on Adverse Neurological Effects of Exposure to Ambient Air Pollution - Xu, Xiaohui; Ha, Sandie Uyen; Basnet, Rakshya (Frontiers in Public Health, 2016)
There is a growing body of epidemiological research reporting the neurological effects of ambient air pollution. We examined current evidence, identified the strengths and weaknesses of published epidemiological studies, and suggest future directions for research in this area. Studies were identified through a systematic search of online scientific databases, in addition to a manual search of the reference lists from the identified papers. Despite being a relatively new area of investigation, overall, there is mounting evidence implicating adverse effects of air pollution on neurobehavioral function in both adults and children. Further research is needed to expand our understanding of these relationships, including improvement in the accuracy of exposure assessments; focusing on specific toxicants and their relationships to specific health endpoints, such as neurodevelopmental disorders and neurodegenerative diseases; investigating the combined neurological effects of multiple air pollutants; and further exploration of genetic susceptibility for neurotoxicity of air pollution. In order to achieve these goals collaborative efforts are needed from multidisciplinary teams, including experts in toxicology, biostatistics, geographical science, epidemiology, and neurology.